Balancing, bandwagoning or hedging: Taiwan's strategic choices in the era of a rising China. (2nd January 2021) - Wang, T.Y.; Tan, Alexander C.
ABSTRACT: Small states have three strategic options when they are confronted by a rising power: balancing, bandwagoning, and hedging. With an increasingly powerful and assertive China as its neighbour, Taiwan, as a small state, is in such a conundrum. Employing survey data collected during the past two decades, this study examines how Taipei's cross-Strait policy has been closely associated with the public's preferences. Because Taiwan citizens reject a unification under Beijing's terms, the bandwagoning policy has never been considered as an acceptable strategy. A 'pure' balancing policy is also unpalatable due to the enormous costs and associated risks. Instead, the island citizens are generally supportive of setting aside the sovereignty dispute with a rapprochement approach towards China. Hedging has thus become a preferred strategic option for most Taiwan citizens. The public's support for a hedging policy has shifted recently due to China's aggressive conduct and America's supportive policy towards Taiwan. Because Beijing's assertive behaviour is expected to persist and the Biden administration will remain supportive of Taiwan, Taipei's strategic choice is likely to have a stronger balancing component. The cold and tense cross-Strait relationship since 2016 is expected to continue beyond the tenure of Taiwan's pro-independence incumbent government.